Deconstruction of Patriarchal Interpretation of the Concept of Nafsin Wahidah in Surah An-Nisa: An Analysis of the Hermeneutics of Tauhid Asma Barlas' Perspective on Gender Equality - Afifah Fitria Nugroho; Auwal Salisu; Moh. Nor Ichwan (Jurnal test, 2025)
This research examines the concept of nafsin wahidah in Surah An-Nisa verse 1 through Asma Barlas's anti-patriarchal theological perspective to address the dominance of classical exegesis that exhibits gender bias. This verse is often used to justify gender hierarchy through the narrative of Eve's creation from Adam's rib, despite the Qur'an not explicitly mentioning this. The significance of this study lies in its attempt to deconstruct the patriarchal legacy within the exegetical tradition that has resulted in social and legal inequalities against Muslim women. This research employs a qualitative approach with text analysis methods based on Asma Barlas's hermeneutics of tawhid, involving linguistic and historical analysis of QS. An-Nisa verse 1, as well as comparisons between classical exegesis and Barlas's approach in Believing Women in Islam. The analysis reveals that nafsin wahidah refers to the non-gendered and equal essence of humanity, rather than representing Adam as a superior male. Barlas dismantles patriarchal assumptions in classical exegesis by demonstrating that the concept of zaujaha emphasizes mutuality, not subordination. The hermeneutics of tawhid developed by Barlas positions the principle of God's oneness as the ethical and theological foundation for understanding gender equality. This research affirms that the Qur'an, when read contextually and justly, supports egalitarian relations between men and women. It is recommended that the hermeneutics of tawhid approach be applied more broadly in exegetical studies to build an inclusive and gender-just Islamic theology.